Carbon dioxide sensing by immune cells occurs through carbonic anhydrase 2-dependent changes in intracellular pH - Strowitzki, Moritz; Nelson, Ross; Garcia, Mario P.; Tuffs, Christopher; Bleul, Marc B.; Fitzsimons, Stephen; Navas, Javier; Uzieliene, Ilona; Ritter, Alina; Phelan, David; Kierans, Sarah J.; Blanco, Alfonso; et al. (The journal of immunology, 2022)
CO2, the primary gaseous product of respiration, is a major physiologic gas, the biology of which is poorly understood. Elevated CO2 is a feature of the microenvironment in multiple inflammatory diseases that suppresses immune cell activity. However, little is known about the CO2-sensing mechanisms and downstream pathways involved. We found that elevated CO2 correlates with reduced monocyte and macrophage migration in patients undergoing gastrointestinal surgery and that elevated CO2 reduces migration in vitro. Mechanistically, CO2 reduces autocrine inflammatory gene expression, thereby inhibiting macrophage activation in a manner dependent on decreased intracellular pH. Pharmacologic or genetic inhibition of carbonic anhydrases (CAs) uncouples a CO2-elicited intracellular pH response and attenuates CO2 sensitivity in immune cells. Conversely, CRISPR-driven upregulation of the isoenzyme CA2 confers CO2 sensitivity in nonimmune cells. Of interest, we found that patients with chronic lung diseases associated with elevated systemic CO2 (hypercapnia) display a greater risk of developing anastomotic leakage following gastrointestinal surgery, indicating impaired wound healing. Furthermore, low intraoperative pH levels in these patients correlate with reduced intestinal macrophage infiltration. In conclusion, CO2 is an immunomodulatory gas sensed by immune cells through a CA2-coupled change in intracellular pH.
Published online April 27, 2022
Gesehen am 04.07.2022